IMPLEMENTASI PERATURAN DAERAH NOMOR 15 TAHUN 2010 TENTANG PAJAK MINERAL BUKAN LOGAM DAN BATUAN PADA BADAN PENDAPATAN DAERAH KABUPATEN TABALONG (p3m.stiatabalong.ac.id, 2022)
The purpose of this study was to find out and analyze how the implementation of Regional Regulation Number 15 of 2010 concerning Taxes on Non-Metal and Rock Minerals at the Regional Revenue Agency of Tabalong Regency. The type and approach of this research is descriptive quantitative using a questionnaire method. The population and sample in this study are non-metallic mineral and rock taxpayers who have paid non-metallic mineral and rock taxes at the Regional Revenue Agency office as many as 35 people. The data collection techniques used were observation, questionnaires and documentation. The data analysis method used is the analysis according to Muhammad Ali by calculating using percentages. The results of this study indicate that the Implementation of Regional Regulation No. 15 of 2010 concerning Taxes on Non-Metal and Rock Minerals at the Regional Revenue Agency of Tabalong Regency is categorized as Adequate in accordance with the applicable regional rules. Keywords: Implementation, Non-Metal and Rock Mineral Tax